2017
DOI: 10.18632/oncotarget.22722
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma hepcidin with mortality risk in patients with coronary artery disease

Abstract: BackgroundIncreased blood hepcidin may be associated with the presence and promotion of atherosclerosis, the association of hepcidin with mortality among coronary artery disease (CAD) patients remains unknown. We sought to assess the relationship of hepcidin and all-cause and cardiovascular disease (CVD) mortality among CAD patients with and without acute coronary syndrome (ACS).Methods and ResultsThis study included 759 patients with ACS and 526 patients with stable CAD. After an average follow-up of 4.1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Similar results were found in a genetic study, in which 12 iron-related genes were assessed [41]. In a large clinical study of 759 patients with ACS and 526 patients with stable CAD, plasma hepcidin was found positively associated with all-cause and CVD mortality in ACS patients [42]. However, other studies have found no significant associations [43,44].…”
Section: Iron Status and Genetic Disorders Associated With Abnormal Isupporting
confidence: 70%
“…Similar results were found in a genetic study, in which 12 iron-related genes were assessed [41]. In a large clinical study of 759 patients with ACS and 526 patients with stable CAD, plasma hepcidin was found positively associated with all-cause and CVD mortality in ACS patients [42]. However, other studies have found no significant associations [43,44].…”
Section: Iron Status and Genetic Disorders Associated With Abnormal Isupporting
confidence: 70%
“…Concerning comorbidities at baseline there was an overrepresentation of cardiovascular disease and chronic kidney disease in the sepsis group which might influence the results. Previous studies have found that hepcidin levels are elevated in patients with acute coronary syndrome, in patients with type 2 diabetes mellitus, as well as in chronic kidney disease, CKD 58 60 . With the low numbers of patients with CKD in our cohort, 17 patients totally, 12 septic and 5 non-septic patients, statistics are not feasible, but median level of hepcidin was 41.5 nmol/L among the septic patients with CKD whereas only 4.7 nmol/L in the non-septic patients, the latter inconsistent with what has been reported on CKD without sepsis 59 .…”
Section: Discussionmentioning
confidence: 98%
“…Hepcidin inhibits cholesterol e ux in macrophages and promotes the progression of facilitate plaque, possibly by iron trapping in macrophages [23] , inducing iron-mediated oxidative stress and increasing foam cell formation [24] . With the death of the iron-laden macrophages, the content of atheromatous plaque increased cytotoxicity to surrounding cellular elements and new monocytes are recruited to the vulnerable atherosclerotic plaque [25] . In animal studies, suppression of hepcidin pharmacologically leaded to reduce intracellular iron content in macrophages and increase macrophage cholesterol e ux, thereby decreased the formation of foam cells and atherosclerosis [26] .…”
Section: Discussionmentioning
confidence: 99%